2020
DOI: 10.3389/fmed.2020.00380
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Activity of Tussilagone via Inhibition of the GPVI Downstream Signaling Pathway in Platelets

Abstract: Tussilagone is a sesquiterpenoid extracted from Tussilago farfara and is used as an oriental medicine for asthma and bronchitis. Although previous studies have shown that tussilagone has an inhibitory effect on platelet aggregation, no studies have been performed to investigate its precise effect on platelets, and the underlying mechanism remains unclear. In the present study, we showed that tussilagone inhibited platelet aggregation induced by collagen, thrombin and ADP, as well as platelet release induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…Many compounds or extracts of plant origin inhibited platelet function and mediated the collagen-induced GPVI signalling pathway. Glaucocalyxin A incubation reduced phosphorylation of SYK, LAT and PLCγ2 (Li et al, 2013); Tussilagone decreased the phosphorylation of Syk/PLCγ2-PKC/MAPK signaling pathways (Zhou et al, 2020); Salidroside inhibits platelet function through AKT/GSK3β signaling pathway (Wei et al, 2020). In the present study, we also demonstrated that pimpinellin inhibited multiple key protein phosphorylation related to collagen-induced signaling pathways in platelets.…”
Section: Discussionsupporting
confidence: 68%
“…Many compounds or extracts of plant origin inhibited platelet function and mediated the collagen-induced GPVI signalling pathway. Glaucocalyxin A incubation reduced phosphorylation of SYK, LAT and PLCγ2 (Li et al, 2013); Tussilagone decreased the phosphorylation of Syk/PLCγ2-PKC/MAPK signaling pathways (Zhou et al, 2020); Salidroside inhibits platelet function through AKT/GSK3β signaling pathway (Wei et al, 2020). In the present study, we also demonstrated that pimpinellin inhibited multiple key protein phosphorylation related to collagen-induced signaling pathways in platelets.…”
Section: Discussionsupporting
confidence: 68%
“…Like ACT017 and Revacept, colchicine treatment has not been linked to bleeding complications. Other potential GPVI related targets, undergoing clinical trials and scientific investigation, have shown decreased platelet responses including aggregation, P-selectin expression and GPIIb/IIIa conformational change in response to multiple agonists, some of these targets are in use for treatment of hematological malignancies ( 68 70 ).…”
Section: Discussionmentioning
confidence: 99%